2021
DOI: 10.3390/educsci11120799
|View full text |Cite
|
Sign up to set email alerts
|

STEM Students’ Perceptions on Emergency Online Learning during the COVID-19 Pandemic: Challenges and Successes

Abstract: Declaration of the COVID-19 pandemic by the World Health Organization in 2020 forced many schools to switch to emergency virtual instruction. This situation provided an opportunity to explore the effectiveness of online learning from students’ perspectives. To discover best practices for online learning, 584 STEM students at California State Polytechnic University Pomona (Cal Poly Pomona) were surveyed about their Spring and Fall 2020 experiences. Some of the obstacles students faced were adapting to a new lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 15 publications
(48 reference statements)
10
29
0
Order By: Relevance
“…In general, students more often than schoolchildren note the advantages of distance learning, with advantages being identified by less than 10% of the student group. The results obtained are consistent with the studies [20,38,[46][47][48], indicating that, in general, students perceive distance learning positively.…”
Section: Discussionsupporting
confidence: 90%
“…In general, students more often than schoolchildren note the advantages of distance learning, with advantages being identified by less than 10% of the student group. The results obtained are consistent with the studies [20,38,[46][47][48], indicating that, in general, students perceive distance learning positively.…”
Section: Discussionsupporting
confidence: 90%
“…Our study respondents reported not only challenges but also benefits of ERL: Increased flexibility and convenience: Like in many other studies, our surveyed students evaluated positively the flexibility and convenience of online learning and its time and space independence [13,14,24,32,63,[106][107][108][109][110]. They also noted that ERL provided them with a safe and comfortable environment for continuing their learning during COVID-19 [31][32][33]111,112].…”
Section: Benefits Of Erl and Suggestions For Improvementsupporting
confidence: 58%
“…? Alangari, (2022) and Selco and Habbak, (2021) emphasize that individual and contextual factors shape perceptions and attitudes of teachers. Therefore, this study specifically examined the relationship between teachers' demographic characteristics, school environment variables and their attitudes towards STEML teaching.…”
Section: What Are the Attitudes Of Ecuadorian Science Teachers Toward...mentioning
confidence: 99%